Morphological Characterzations of Spinel Nanoparticles Synthesized by Sol- Gel Method. Issue 1 (August 2021) - Edrees, Shaker J.; Kareem, Shaima'a J.; Fadel, Al-Khader Mohammed
Abstract: In this paper, pure magnesium alumina ( MgAl 2 O 4 ) and magnesium alumina spinel nanoparticles doped iron ( MgAl 2- X Fe X O 4 ) where (X= 0.01, 0.02, 0.03, 0.04, 0.05) were by sol-gel method. The calcination operation was performed at a temperature of 800 ° C at a rate of 5 ° C/min. The resulting materials of MgAl2-X FeX O4 nanoparticles were determined using, , XRD, FT-IR, EDX, SEM methods. XRD results show that MgAl 2 O 4 and Fe +3 : MgAl 2 O 4 nanoparticles have a single-phase at 800 ° C. FTIR analyze confirmed the presence of MgAl 2 O 4 and Fe +3 : MgAl 2 O 4 as well as FTIR analysis shows its composition and structure. Surface morphology examinations by scanning electron microscopy (SEM) show that the nanoparticles synthesized in this way are estimated to be angular, uniform and about 50-70 nm in size.